Pengaruh Indeks Harga Saham Gabungan (IHSG), Volume Perdagangan dan Risiko Sistematik Terhadap Harga Saham (Studi Kasus pada Perusahaan Manufaktur Sektor Properti, Real Estate Dan Building Construction yang Terdaftar Dalam BEI Tahun 2015-2019) - Siti Nur Latifah; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstrackThis study aims to find out how the composite stock price index (CSPI), trading volume, and systematic risk to stock prices (case study in manufacturing companies in the property, real estate, and building construction sectors listed on the Indonesia Stock Exchange in 2015-2019). In this study, there are 3 (three) independent variables that are used to measure stock prices, namely the composite stock price index (CSPI), trading volume, and systematic risk. And the dependent variable in this research is the stock price. The population in this study were all property, real estate, and building construction companies listed on the Indonesia Stock Exchange in the 2015-2019 period with a total of 89 companies and the sample in this study was taken using a purposive sampling technique, namely the selection of sample members based on certain criteria and obtained a sample of 16 companies property, real estate, and building construction. The data collection method used is the documentation method by recording or documenting data listed in the annual report on (IDX). The data analysis technique used in this study is the simple linear regression. The results of the study stated that JCI partially had a significant positive effect on stock prices. Partial trading volume has a significant negative effect on stock prices. And Systematic Risk partially there is a significant negative influence on stock prices.Keywords: Composite Stock Price Index (CSPI), Trading Volume, Systematic Risk, Stock Prices